Emotional regulation in the classroom: detection of multiple cases from systematic observation - Alarcón-Espinoza, Marina; Samper, Paula; Anguera, M. Teresa (Frontiers in Psychology, 2024)
Emotional education is learned by living with others. This study analyzes how different actors participate in the classroom, influencing students' emotional regulation. Using a mixed methods approach [structured in macro-stages QUAL-QUAN-QUAL], 9 classes in three Chilean schools with children aged 10 to 12 are systematically observed. The audio-recorded sessions are transcribed (qualitative data) for coding from the observation instrument, and then, once the data quality is verified, they are analyzed quantitatively (quantitizing). A lag sequential analysis is performed to detect regularities and existing sequences, and a polar coordinate analysis is performed to observe the relationships among the categories in each class. Once the results of the analyses have been obtained, similarities are sought to detect the presence of multiple cases based on the two analysis techniques. The multiple cases detected are presented, detailing how interactions between teachers and students contribute to the emotional regulation and climate in the daily life of the classroom. The interpretation of the results makes it possible to revisit the qualitative aspect of the mixed methods and to discuss the need to problematize the role of teachers in students' development and autonomy.